Factors related to intention to stop being homeless among homeless people in Kuala Lumpur, Malaysia - Abu Bakar, Nur Syazwani (2016)
In Malaysia, the number of people became homeless have increased every year in reprisal to high cost of living and economic growth. The purpose of this study is to examine homeless intentions to quit of being homeless by investigating the TPB variables: attitudes, subjective norm, and perceived behavioral control, along with internal and external factors of homelessness. The study involved a total number of 220 homeless people from four different locations in Kuala Lumpur which is Masjid Jamek, Jalan Panggung, Masjid Negara, and Jalan Sultan Ismail. In describing the relationship between variables, theory of planned behavior has been adopted. This study focuses on other added variables such as internal and external factors, other than existing variables included in the theory which is attitude, perceived behavior control,and subjective norm to predict intentions to quit of being homeless. Findings from this study show that gender, age, and years being homeless were able to predict intention to quit of being homeless and concluded that there were statistically significant differences between female and male and also between age group. However, between of years of being homeless group, the differences in those variables were not significant. The results show that scores from most of the respondents were classified under moderate level in this study for all of the variables tested. Furthermore, the results showed, all the variables had significant relationship with intention. In this study, it is revealed that the subjective norm was a unique predictor of intention to quit of being homeless. Findings from this study suggest that internal and external factors play a significant role in predicting intention among homeless people to quit of being homeless in Kuala Lumpur. Homeless exposure to community influences particularly on community expectation towards them. This study provides valuable information on how society could act in order to help the homeless people on their intention to quit of being homeless.